1998
DOI: 10.2214/ajr.171.2.9694485
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-enhanced MR imaging of temporomandibular disorders: improved lesion detection of the posterior disk attachment on T1-weighted images obtained with fat suppression.

Abstract: OBJECTIVE. The purposeof this studywas to assessthe potentialfor improvedlesion detection in the posterior disk attachment and its surrounding tissue in temporomandibular disorderswhengadolinium-enhanced MR imagingperformedwith fat suppression is used. MATERIALSAND METHODS. Forty-five patients underwent MR imaging withconventional Ti-and T2-weighted, gadolinium-enhanced Ti-weighted, and gadolinium-enhanced fat suppressed spin-echo imaging sequences. Qualitative and quantitative assessments of the contrast enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…In the present study, we used a fat-suppressed T1-weighted FSE sequence to obtain the contrast enhancement of the posterior disk attachment. Our previous study indicated that the effectiveness of contrast enhancement with a T1-weighted FSE sequence was superior to that with a spoiled gradient-echo sequence [57]. In the synovial membrane tissue of the posterior disk attachment region and the TMJ capsule, more highly innervated and inflamed tissues are sources and causes of greater pain [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used a fat-suppressed T1-weighted FSE sequence to obtain the contrast enhancement of the posterior disk attachment. Our previous study indicated that the effectiveness of contrast enhancement with a T1-weighted FSE sequence was superior to that with a spoiled gradient-echo sequence [57]. In the synovial membrane tissue of the posterior disk attachment region and the TMJ capsule, more highly innervated and inflamed tissues are sources and causes of greater pain [58].…”
Section: Discussionmentioning
confidence: 99%
“…T2-weighted fat-suppressed MR imaging was used to evaluate the T2-weighted SI of the posterior disk attachment, because the area is abundant in fatty tissue [8]. In an earlier study, we demonstrated that the effectiveness of contrast enhancement is often limited by fat tissue for components such as the posterior disk attachment and mandibular condyle [57]. The presence of fat tissue is greatly problematic for evaluating the correlation between the severity of pain symptoms and the degree of contrast enhancement of the posterior disk attachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty tissue within the posterior disk attachment and lateral pterygoid muscle has high signal intensity on T1-weighted MR images and occasionally obscures anatomic structures in the TMJ region by means of chemical artifact [50]. Therefore, dynamic fat-suppressed MR imaging with contrast material appears to be highly sensitive for the diagnosis of posterior disk attachment abnormalities.…”
Section: Pathological Posterior Disk Attachment-related Joint Painmentioning
confidence: 99%
“…Therefore, FS T1-weighted images may be used to distinguish between periarticular fatty tissue and synovial tissue. 15,16 It has also been reported that FS T1-weighted images are highly eective for the evaluation of bone marrow lesions, including those of the mandible. 10,15,17 The aims of this study are to (1) compare FS T2-weighted imaging versus conventional sequences for the detection of joint eusion in the TMJ and (2) to determine if an association exists between TMJ eusion (FS T2-weighted images) and bone marrow abnormalities and disk displacements.…”
Section: Introductionmentioning
confidence: 99%